Transformasi Pemenuhan Adat Pernikahan Suku Dayak Siang : Perspektif Antropologi Hukum Islam - Syahroni, Akhmad; Helim, Abdul; Tanjung, Ardi Akbar; Wahdini, Muhammad (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
Koroketon Beti is a customary gift that a prospective groom is obligated to give to his bride-to-be, equivalent to the Islamic concept of a dowry. The Regulations of Dayak Siang Murung Customary Law in Murung Raya Regency stipulate in Article III that Koroketon Beti can be fulfilled through a monetary payment. This research aims to investigate the shift from the traditional requirement of providing specific goods to the current practice of monetary fulfillment in this customary law. This study employs a normative legal research approach, focusing on the inventory of Dayak Siang customary law and Islamic law in Tanah Siang District, Murung Raya Regency, Central Kalimantan Province. The research findings indicate that the provision of Koroketon Beti in customary marriages is a mandatory requirement and a sign of respect from the prospective groom to the bride. This shift reflects the inevitable dynamics of culture, which must be managed wisely to preserve traditional values in modern life. Textually, Islamic law does not mandate the provision of Koroketon Beti; instead, it requires a dowry. However, the practice of providing Koroketon Beti is permissible as it does not contradict Islamic law and has been a long-standing custom.